Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 7 - Review: 37



Work Step by Step

$\dfrac{4}{x+3}-2$ Evaluate the substraction and simplify if possible: $\dfrac{4}{x+3}-2=\dfrac{4-2(x+3)}{x+3}=\dfrac{4-2x-6}{x+3}=...$ $...=\dfrac{-2x-2}{x+3}=...$ Take out common factor $-2$ to provide a more simplified answer: $...=-\dfrac{2(x+1)}{x+3}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.